The Semiotics of Titling in Very Short Poems: A Study of Contemporary Gulf Poetry Models - Aldhafeeri, Musaad Kareem Jaber (Journal of Arabic Language Sciences and Literature, 2024)
This study aims to read the title and uncover its semiotics in very short poems within contemporary Gulf poetry models. The study seeks to analyze the initial threshold and demonstrate the relationship between titling and the very short poetic text. Titling in these condensed texts opens up multiple horizons for the text and the recipient, providing ample space to make the text open to several readings as a result of the sender's intention in choosing the title, which represents the initial communication with the recipient. The study seeks to engage with the text and explore the features of titling within its parts, and to measure the extent of communication between titling and the very short poetic text. Titling in the very short poem has utilized multiple patterns suggesting psychological, iconic, poetic, and other dimensions, which allows the text to move in parallel with the titling pattern and its semiotics.
Keywords: Semiotics of titling; title; very short poem; poetic titling